Energy for a sustainable world : from the oil age to a sun-powered future - Armaroli, Nicola; Balzani, Vincenzo (Weinheim, German : Wiley-VCH Verlag GmbH, 2011)
"This book surveys the energy issue from a broad scientific perspective while considering environmental, economic, and social factors. It explains the basic concepts, provides a historical overview of energy resources, assesses our unsustainable energy system based on fossil fuels, and shows that the energy crisis is not only a tough challenge, but also an unprecedented opportunity to become more concerned about the world in which we live and the society we have built up. By outlining the alternatives for today and the future, it gives an extensive overview on nuclear energy, solar thermal and photovoltaics, solar fuels, wind power, ocean energies and other renewables, highlighting the increasing importance of electricity and the long-term perspectives of a hydrogen-based economy"--Back cover.
Includes bibliographical references (p. 318-352) and index.
Keywords: Power resources; Energy development; Energy policy; Sustainable development; Energy conservation